2001
DOI: 10.1007/s11627-001-0040-z
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of genetic fidelity of In vitro-raised Lilium bulblets through rapd markers

Abstract: Random amplified polymorphic DNA (RAPD) markers were utilized for screening the clonal fidelity of in vitro-raised bulblets of Lilium sp. (Asiatic hybrids) produced through adventitious mode of propagation. The first set of 14 bulblets was randomly chosen from about 175 micropropagated bulblets regenerated from 1 Â 1 cm 2 bulbscale segments (explants) of cultivar`Gran Paradiso' after four subcultures (after 6 mo.). The second set of 15 bulblets was selected again randomly after 12 subcultures (after one and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 28 publications
1
20
0
2
Order By: Relevance
“…The general belief is that multiplication involving a callus phase is more vulnerable for DNA damage during micropropagation [24,25]. For an example; in oil palm (Elaeis guineensis Jacq), 5% of somatic embryo-derived palms showed an abnormality that is called the 'mantled' phenotype [26].…”
Section: Resultsmentioning
confidence: 99%
“…The general belief is that multiplication involving a callus phase is more vulnerable for DNA damage during micropropagation [24,25]. For an example; in oil palm (Elaeis guineensis Jacq), 5% of somatic embryo-derived palms showed an abnormality that is called the 'mantled' phenotype [26].…”
Section: Resultsmentioning
confidence: 99%
“…No polymorphism was detected during the RAPD and ISSR analysis of in vitro-raised clones. The absence of genetic variation using RAPD and ISSR marker has been reported in micropropagated shoots of Pinus thunbergii (Goto et al 1998) and swertia (Joshi and Dhawan 2007), in vitro-regenerated turmeric (Salvi et al 2001), and in vitro-raised bulblets of Lilium (Varshney et al 2001). …”
Section: Discussionmentioning
confidence: 99%
“…Molecular marker analysis of micropropagated plants has been reported in several plant species (Bhatia et al 2011;Goto et al 1998;Salvi et al 2001;Varshney et al 2001). Martins et al (2004) reported the genetic stability of micropropagated almond plants.…”
Section: Discussionmentioning
confidence: 99%